Факторы национальной идентичности, толерантности, ксенофобии и антисемитизма в современной Украине - Панина, Н. (Социология: теория, методы, маркетинг, 2005)
The author of this article has distinguished on the basis of Bogardus social distance scale the following levels of national distance: identity, tolerance, estrangement, isolationism, and xenophobia. The analysis of sociological monitoring (1992–2005) data concerning national distance of Ukraine’s population allows revealing the growth of all national isolationism and xenophobic attitudes. On the results of survey has been conducted in 2005 regional, demographic, political, and socioeconomic factors determining the peculiarities of interethnic attitudes are analyzed. Tendencies and factors of general national distance are studied with the attitudes of different groups of Ukraine’s population to the representatives of the other nations, such as Ukrainians, Russians, Americans, and Jews.